The truth about bats - Moore, Eva.; Enik, Ted (New York : Scholastic, 1999)
The students of the Magic School Bus learn the scientific facts as well as the myths about bats.
"Based on the Magic School Bus books written by Joanna Cole"--T.p. verso.
4.0
3-6
Keywords: Bats -- Fiction; Bats -- Fiction